Evaluation of Two Irrigation Scheduling Methods and Nitrogen Rates on Corn Production in Alabama. (15th September 2020) - Da Cunha Leme Filho, Jose Franco; Ortiz, Brenda V.; Balkcom, Kipling S.; Damianidis, Damianos; Knappenberger, Thorsten J.; Dougherty, Mark
Abstract : Regulations on nutrient application amounts and environmental impacts of fertilizers are promoting advances in agricultural management strategies to optimize irrigation application and N fertilization in corn. Previous studies have found a relationship between irrigation application, available water in the soil, and N fertilizer uptake. The objective of this study was to evaluate interactions between two irrigation scheduling methods and four N rate applications (0-control, 202, 269, and 336 kg ha −1 ) on grain yield, aboveground biomass, plant N concentration, N uptake, and nitrogen use efficiency in corn. The study was conducted at the Tennessee Valley Research and Extension Center (TVREC) during two growing seasons (2014 and 2015). The irrigation scheduling methods consisted of (i) the pan evaporation method, which is based on managing the crop's estimated evapotranspiration (ET) using pan evaporation values and the crop's consumptive water use and (ii) the sensor-based irrigation scheduling method based on soil matric potential values recorded by soil moisture tension sensors installed in the field. Irrigation amounts from both irrigation scheduling methods indicated that less water was applied with the sensor-based method. The different amounts of irrigation applied associated with the two irrigation scheduling methods did not impact grain yield, aboveground biomass, and NUE. In general, NUEs values decreased with increased N rates, which means that additional N fertilizer added to the soil was not converted into grain yield or/and adsorbed by plants; therefore, more N remained in the soil, increasing the risk for environmental problems.